Control of mechanical pain hypersensitivity in mice through ligand-targeted photoablation of TrkB-positive sensory neurons - Dhandapani, Rahul; Arokiaraj, Cynthia Mary; Taberner, Francisco J.; Hussain, Ahmad Fawzi; Barth, Stefan; Johnsson, Kai; Lechner, Stefan; Heppenstall, Paul A. (Nature Communications, 2018)
There are several classes of sensory neuron that contribute to pain states. Here, the authors demonstrate that TrkB+ sensory neurons detect light touch under normal conditions in mice but contribute to hypersensitivity in models of chronic pain, and that ligand-guided laser ablation of TrkB+ sensory neurons in the mouse skin attenuates this hypersensitivity.